External Morphological Study of Tribolium castaneum (Herbst , 1797) (Coleoptera : Tenebrionidae) mid of Iraq - Zainab H. Salman; Hassan S. Al-Asady; Ayad A. Al-Taweel (Journal of Madenat Alelem University College, 2018)
The study included the description of external body parts and the male genitalia for the male of rusty flour beetle Tribolium castaneum (Herbst,1797) and the studied was supported by illustrations.